2021
DOI: 10.3390/ijerph18157967
|View full text |Cite
|
Sign up to set email alerts
|

VCI-Based Analysis on Spatiotemporal Variations of Spring Drought in China

Abstract: The analysis of spatiotemporal variations in drought is important for environmental monitoring and agricultural production. In this study, the spring vegetative drought conditions in China were analyzed by using the vegetation condition index (VCI) as an indicator to reveal the drought characteristics in China from 1981–2015. The results suggest that spring vegetative drought (especially moderate drought) occurs frequently in China, and drought conditions have obvious geographical differences and are highly af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Different from the EVI, which directly measures vegetation growth state, the VCI reflects how many differences there are between vegetation status and background value in a given area and can identify drought conditions based on local climate and natural background conditions. It has the potential to mitigate the effects of geographical, climatic and soil factors [17,55]. Therefore, VCI is frequently used to diagnose drought and quantify its onset, severity, duration, and effect on vegetation [56].…”
Section: Vegetation Condition Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from the EVI, which directly measures vegetation growth state, the VCI reflects how many differences there are between vegetation status and background value in a given area and can identify drought conditions based on local climate and natural background conditions. It has the potential to mitigate the effects of geographical, climatic and soil factors [17,55]. Therefore, VCI is frequently used to diagnose drought and quantify its onset, severity, duration, and effect on vegetation [56].…”
Section: Vegetation Condition Indexmentioning
confidence: 99%
“…This might be because the SPI/SPEI only measures the meteorological drought, but the VCI/WVCI reflects the comprehensive impacts of meteorological drought on vegetation, including precipitation, temperature, evaporation, vegetation type, and so on. The PDSI is similar to the VCI in that it takes temperature, humidity, evaporation and recharge rate into account [55]. As a result, VCI/WVCI can more accurately reflect the real impacts of drought on vegetation than SPI/SPEI.…”
Section: Relationship Between Wvci and Vcimentioning
confidence: 99%
“…The yearly precipitation is less than 158 millimeters. Hotian and Aksu are main rivers in the region (Liang et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
“…However, other factors also influence vegetation growth [10,38,78,79], such as solar radiation or sunlight hours, soil moisture, etc. For example, previous studies [80,81] have reported that drought-induced soil water deficit is often a…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…However, other factors also influence vegetation growth [10,38,78,79], such as solar radiation or sunlight hours, soil moisture, etc. For example, previous studies [80,81] have reported that drought-induced soil water deficit is often a main factor affecting vegetation growth. The influence of other factors on vegetation change should be considered in future studies.…”
Section: Limitations and Implicationsmentioning
confidence: 99%